Opioid Prescribing after Carpal Tunnel Release: Analysis from the Michigan Collaborative Hand Initiative for Quality in Surgery. Issue 5 (November 2021) - Billig, Jessica I.; Kotsis, Sandra V.; Chung, Kevin C.
Abstract : Background: Little is known regarding the national practice patterns for postoperative opioid prescribing after carpal tunnel release, which is one of the most common surgical procedures performed. The authors sought to assess the rate of opioid prescribing after carpal tunnel release and patient-, surgeon-, and practice-level predictors of opioid prescriptions after surgery. Methods: The authors conducted a cohort study from the Michigan Collaborative Hand Initiative for Quality in Surgery, a national consortium of nine practices with 33 surgeons who prospectively collect data for the purpose of quality improvement. Patients were included who underwent carpal tunnel release between July 1, 2019, and December 31, 2019. Multilevel logistic regression was used to determine practice and surgeon variation in postoperative opioid prescribing related to patient characteristics. Results: Of the 648 patients with 792 operative hands, 52.9 percent were prescribed a postoperative opioid. After controlling for patient, surgeon, and practice characteristics, endoscopic carpal tunnel releases were associated with a decreased odds of receiving a postoperative opioid prescription compared to open carpal tunnel releases (OR, 0.19; 95 percent CI, 0.07 to 0.52). However, 57.4 percent of the variation in opioid prescribing was explained at the practice level, and 4.1 percent of the variation was explained at the surgeon level. Conclusions: Practice-level prescribing patterns play a substantial role in opioid prescribing. National efforts should consider development of evidence-based opioid prescribing recommendations for carpal tunnel release that target all prescribers, including trainees and advanced practice providers. In addition, endoscopic carpal tunnel release may offer an opportunity to minimize opioid prescribing. The authors recommend that providers encourage the use of nonopioid analgesia and limit opioid prescriptions after carpal tunnel release. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.